A systematic review of the role of interleukin-17 and the interleukin-20 family in inflammatory allergic skin diseases. Issue 5 (October 2016) - Hofmann, Maja A.; Kiecker, Felix; Zuberbier, Torsten
Abstract : Purpose of review: Allergic skin diseases include atopic dermatitis/eczema, contact dermatitis, and drug hypersensitivity. Allergic skin diseases have a high prevalence. Atopic dermatitis is one of the most common inflammatory skin diseases and similar for allergic rhinitis and allergic asthma. Over a long period, allergic diseases have been regarded as immunoglobulin E-mediated T-helper-2 (Th2)-driven. But new cytokines and T cells have been discovered within the last years. In this systematic review, the focus is laid on interleukin-17 (IL-17) and the interleukin-20 (IL-20) family which appear to be fine-tuning the Th2-driven answer. Recent findings: IL-17 is a proinflammatory cytokine, which is produced by T cells. Primarily, IL-17 is produced by activated CD4+ cells, called Th-17 cells. IL-17 regulates keratinocyte expression of adhesion molecules and chemokines. IL-17 is involved in the pathogenesis of inflammatory diseases as psoriasis, arthritis, and inflammatory bowel diseases. In allergic diseases, the involvement of the TH17/IL17-pathway has only been recently described. Regarding the IL-20 family, IL-22 is the most interesting and the most studied cytokine in terms of allergic inflammatory disorders. IL-22 is produced by T-helper 22 cells, a new subset of CD4+ cells. Summary: IL-17 as well as IL-22 seem to play a role in the pathogenesis of allergic skin diseases.